The breakdown of hierarchy : communicating in the evolving workplace - Marlow, Eugene (Butterworth-Heinemann, 1997)
The Breakdown of Hierarchy explores the changes that have taken place in the second half of the 20th century and how organizations of all sizes can harness electronic media to open the lines of dialogue and corporate conversation. Never before published case studies of Honeywell, Motorola and Raychem are discussed. Eugene Marlow has been involved with the strategic application of print and electronic media for over 25 years. He has consulted to dozens of organizations in the media, technology, healthcare, consumer products, and non-profit sectors. Dr. Marlow teach.